Pengaruh Penggunaan Media Gambar Terhadap Keaktifan Siswa Kelas VII SMP Negeri 1 Sipoholon Mata Pelajaran Pendidikan Agama Kristen Dan Budi Pekerti Tahun Pembelajaran 2023/2024 - Juwita Rajagukguk; Taripar Aripin Samosir; Grecetinovitria M. Butar-Butar; Senida Harefa; Nurelni Limbong (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The aim of this research is to determine the positive and significant influence of using image media in Christian Religious Education and Character Education subjects on the Activeness of Class VII Students at SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year. The method used is a quantitative research method. The population is all class VII students of SMP Negeri 1 Sipoholon for the 2023/2024 academic year, totaling 160 people and a sample of 32 people was determined. The sample in this research was class VII-2, a total of 32 people with the sampling technique used, namely selecting the sample deliberately. (purposive sampling). By using a pre-experimental research design with the form of a one-group-pretest-posttest design. Data was collected using 30 positive closed questionnaire items for variable Y. The results of data analysis showed that there was an influence of the use of image media on the activity of class VII students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year: The significant influence test (t test) obtained a value of t = -43 .9024 < ttable (α=0.025, dk=n-1=31) = -2.039. So H0 is rejected and Ha is accepted.